The joint effect of cumulative doses for outdoor air pollutants exposure in early life on asthma and wheezing among young children - Shuoxin Bai; Jiatao Zhang; Liangliang Cui; Shuang Du; Shaoqian Lin; Yuxiu Liang; Yi Liu; Zhiping Wang (Ecotoxicology and Environmental Safety, 2024)
Background: Constrained by no proper way to assess cumulative exposure, the joint effect of air pollution cumulative exposure doses on childhood asthma and wheezing (AW) was not understood. Objective: To assess the association between cumulative exposure to multiple air pollutants in early life and childhood AW. Methods: We designed a nested case-control study based on the birth cohort in Jinan City. Children with AW followed up within 2 years after birth were treated as cases, and non-cases in this cohort were treated as the control source population, and the propensity score matching method was used to match each case to 5 controls. We calculated the individual cumulative outdoor exposure doses for each period using an inverse distance weighted model, alongside the complex Simpson's formula, accounting for outdoor time and respiratory volume. The Least absolute shrinkage and selection operator (Lasso) regression was performed to screen for covariates. To analyze the joint effects of pollutants, we employed the weighted quantile sum (WQS) regression model in conjunction with conditional logistic regression. Results: 84 cases and 420 controls were included in this study. The odds ratio (OR) with 95% confidence interval (CI) of the impact of cumulative exposure (mg/m3) after birth on childhood AW was 1.78 (1.15–2.74) for SO2, 1.69 (1.11–2.57) for NO2, and 1.65 (1.09–2.52) for PM2.5, respectively. Furthermore, with each 25th percentile increase in the WQS index, the overall risk of cumulative doses for six pollutants exposure after birth on AW increased by an adjusted OR of 1.10 (1.03, 1.18), and SO2, PM2.5, and NO2 contributed the most to the WQS index. However, no statistically significant association was found between cumulative exposure to all pollutants before birth and childhood AW. Conclusions: There was a joint effect of the cumulative exposure dose of outdoor air pollutants after birth on AW in children aged 0–2 years. And traffic-related pollutants (SO2, PM2.5, and NO2) make a greater contribution to the joint effect.